Formation of (Xe2H)* centers in solid Xe via recombination: nonstationary luminescence and «internal electron emission» - Savchenko, E.V.; Khyzhniy, I.V.; Uyutnov, S.A.; Gumenchuk, G.B.; Ponomaryov, A.N.; Beyer, M.K.; Bondybey, V.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The formation of excimers (Xe2H)* in solid Xe doped with molecular hydrogen under electron beam is studied using the original two-stage technique of nonstationary (NS) cathodoluminescence (CL) in combination with the current activation spectroscopy method — thermally stimulated exoelectron emission (TSEE). Charged species were generated using a high-density electron beam. The species produced were then probed with a lowdensity beam on gradual sample heating. The near UV emission of the (Xe2H)* was used to monitor the neutralization process. It is found that the temperature behavior of the NS CL band of (Xe2H)* clearly correlates with the yield of TSEE measured after identical pre-irradiation of the sample. The fingerprints of the thermally stimulated detrapping of electrons — «internal electron emission» in the spectrum of NS CL point to the essential role of neutralization reaction in the stability of the proton solvated by rare-gas atoms.